Seed-Fruit Multiomics Integration of Sweet Cherry Cultivars with Different Maturity Time Shows Alternative Molecular Landscapes at the Transition from Development to Ripening, Unveiling a Role of Small Rnas, Spls, Lignin and Inositol Pathways - Maldonado-Soto, J (Elsevier B.V., 2025)
Several signals control fruit ripening, including hormones and metabolites, many of which are produced by the seeds. However, the molecular signatures of seeds and fruits at the transition from development to ripening (t-DtoR) have not yet been elucidated in non-climacteric species. Thus, we aimed to characterize sweet cherry fruits and seeds through directed hormone profiling, untargeted metabolomics, as well as mRNA-seq and small RNA-seq. The early- and late-season cultivars, ‘Celeste’ and ‘Regina’ respectively, were analyzed at the t-DtoR, where ‘Regina’ had delayed ripening evolution, accompanied by a higher content of negative ripening markers in fruits, such as amino acids and chlorophylls, whereas ‘Celeste’ had more positive markers, including abscisic acid (ABA) and D-Fru. PCA analysis revealed that jasmonic acic (JA) and JA-Ile mostly contributed to clustering according to cultivar. Overrepresentation of ‘auxin response’ and ‘inositol catabolic process” categories occurred in ‘Celeste’ fruits (CF), whereas ‘lignin catabolic process’ was overrepresented in ‘Celeste’ seeds (CS). Higher sugar content, enriched ‘disaccharide metabolic process’ category plus increased levels of cytokinins and gibberellins were distinguishable features of CS. Target search and degradome networks showed several squamosa promoter-binding-like (SPL) encoding sequences abundant in fruits, which were predicted targets of miRNA156s. Interactome networks of the four omics datasets revealed alternative molecular landscapes in the contrasting cultivars, where small RNAs had multiple associations. For instance, the small RNAs mes-miR535d/ csi-MIR166f (‘Celeste’) and gra-MIR8771d/ csi-MIR166f (‘Regina’) had associations with several hormones and transcripts. The gene ontology (GO) analysis of these transcripts showed overrepresentation of ‘response to cytokinin in ‘Celeste’ and ‘auxin response’, in ‘Regina’, respectively. This evidences differences between cultivars at the t-DtoR. Finally, in the interactome seed-fruit connections were identified, with a putative inositol oxidase expressed in fruits having several connections with seed transcripts but only in the early-phenotype. This work highlights small RNAs, SPLs, lignin and inositol pathways as novel players in non-climacteric ripening. © 2025
Keywords: Fruit ripening; MicroRNA; Small RNAs; Sweet cherry; Omics; RNA-seq; Seed